THE LEADING PARADIGM OF TELEVISION ADVERTISING DIRECTION RESEARCH / ВЕДУЩИЕ ПАРАДИГМЫ ИССЛЕДОВАНИЯ РЕЖИССУРЫ ТЕЛЕВИЗИОННОЙ РЕКЛАМЫ - LITOVCHIN Y.M. / ЛИТОВЧИН Ю.М. (Наука телевидения)
The article presents the leading paradigm of television advertising direction research study: communicative, semiotic, aesthetic and cultural ones. Within the communicative paradigm there are being described the possibilities of television advertising through aesthetic-artistic image to simulate the behavior of the viewer, to create the system of «optional» values, defining the mechanisms of psychological influence on the buyer. The study of advertising in line with the semiotic paradigm reveals the ability of the meta-language to communicate different kinds of information to the user. In the context of aesthetic-cultural paradigm advertising is considered as a cultural object, being characterized by trends and thematic diversity of contemporary advertising.